Effect of Reliability, Empathy and Physical Evidence on Satisfaction and Loyalty Seekers Society Birth Certificate At the Department of Population and the Civil Registry Ngawi - Wibiarko, Chandra (STIE AUB Surakarta)
This study aims to determine the effect Reliability, Empathy and Physical Evidence to the satisfaction and loyalty Seekers Society birth certificate in the Department of Population and Civil Registration Ngawi. The technique of collecting data using questionnaires, the sample used is a birth certificate search people in the Department of Population and Civil Registration Ngawi totaling 100 people. The data analysis technique used is path analysis (path analysis), which will be tested by t test, F test and R2, Correlations, direct effect and the indirect effect and the total effect. T test results can be concluded that the Reliability effect positive and significant impact on satisfaction, Empathy influential negative and insignificant to satisfaction, physical evidence a positive influence and significant to satisfaction, Reliability effect positive and significant impact on loyalty, empathy positive influence and significant impact on loyalty, physical evidence and significant negative effect on loyalty, satisfaction and significant negative effect on loyalty. The test results simultaneously (Test F) summed together variable reliability, empathy and physical evidence affecting loyalty. The test results showed that the coefficient of determination R-square value of a total of 0.737, meaning that the variable is explained by the reliability community loyalty, empathy and physical evidence to the satisfaction of the community as an intervening variable amounted to 73.7% and the remaining 26.3% described other factors outside the research model , Results of path analysis showed that based on the analysis of the direct effect (direct effect) and the indirect effect (indirect effect) shows that the direct effect of reliability, empathy and bikti physical loyalty greater than the effect of reliability, empathy and bikti physical loyalty through satisfaction.Keywords: Reliability, Empathy, Physical Evidence, Loyalty, Satisfaction